PERANCANGAN APLIKASI BIMBINGAN BELAJAR ONLINE - Jadiaman Parhusip; Widiatry Widiatry; Indes Permatahati Parhusip (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
The enthusiasm of students to join online tuition centers is rising from time to time. It affects the number of tutors who have the important roles as the instructors. In the meantime, the students usually get information regarding the tuition centers from their colleagues or relatives. This affects the number of the students which is still minor. This indicates that the information about the existence of online tuition centers among societies has not been spread out widely. Mirroring on the lack, there is an idea appears. It is necessary to design a specific website for the online tuition centers. Besides its function as the promotion media, the website also provides access to learning materials. The learning materials which will be offered include theories, academic data manager and tabulation, and exercises with the tricks of how to finish them easily. This aims to help the students improve their achievements at school. The design of the application of these online tuition centers was constructed by the language program of PHP, MySQL basis data, and the methodology of waterfall. All stages of waterfall were started from analysis systems with business process, system design with DFD which includes diagram context, DFD Level 1, and DFD Level 2, ERD, and Data Dictionary. The process of managing and tabulating data which are in the system includes administrators, instructors, applicants and parents, where everyone has the access to the specific features. Through the Blackbox testing, it is concluded that all the features ran well, so they met the plan